2 Answers | Add Yours
(3x-1)(3x-1) + 1 = 5(3x-1)
9x^2 -6x + 1 +1=15x-5
9x^2 -21x +2 = - 5
9x^2 -21x +7 = 0
( )( )=0
check the equation--it doesn't factor--see if you wrote it down right please-- I think you meant = negative 5--then it would work fine
then send it back to me . . .I love doing these things
Mutiply by the denominator (3x-1) to get rid of the fractional form.
9x^2-21x+7 is a quadratic equation of the form ax^2+bx+c=0 whose roots are given by
a=9,b=-21 and c=7. Substing in the quadratic equation we get the roots:
x= [-(-21) +or- sqrt(21^2-4*9*7)}/(2*9}
x=[7+sqrt21]6 or x=[7-sqrt21]/6
x=1.9304approximately, or x=0.4029 approx.
You can put back int he original equations
We’ve answered 395,949 questions. We can answer yours, too.Ask a question